Morphometric Analysis of the Mental Foramen from Bony Landmarks in Dry Human Mandibles - Suman Kumari; , Rajendra Prasad (Academia Anatomica International, 2020)
Introduction:Mental foramina are located bilaterally in the antero-lateral aspect of the body of mandible. It transmits mental nerve, and vessels. The location, shape, size, direction and number of mental foramen in human mandibles are subject of variation. Aims and Objective: To establish the location, shape, size, direction and incidence of mental foramen (MF) in dry human mandibles.Subjects and Methods:One hundred dry human mandibles of unknown age and sex were selected randomly. Shape, size, position of MF with respect to tooth and other anatomical landmark were determined. Paired t-test was used for specific statistical analysis.Results:In most cases (61%), the MF was oval in shape & situated below the apex of second premolar (58% on right side and 69% on left side). Various parameters investigated were, the horizontal distance between (1) base of mandible and MF was 12.24 mm on right and 12.26 mm on the left, (2) alveolar margin and MF was 13.95 mm on right and13.75 mm on left (3) symphysismenti of mandible and MF was 26.71 mm on right and 26.49 mm on left, (4) posterior border of mandible and MF was 65.34 mm on right and 65.68mm on left.Conclusion:By the knowledge of position, shape, size, direction and distance of the mental foramen from various landmarks and the presence of the accessory foramen may be of much use to surgeons.